2020
DOI: 10.31234/osf.io/rjp5a
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological problems associated with coping strategies: a web-based study in Peruvian population during the COVID-19 pandemic

Abstract: ABSTRACT:BACKGROUND: The Coronavirus disease has quickly spread to all corners across Latin-American countries. Its exponential capacity has overwhelmed even the most resilient health systems (1). The already significant impact of the Coronavirus (COVID-19) on the global scale is worsened by psychological responses that may aggravate the health crisis. OBJECTIVE: This study is aimed at collecting demographic information, prevalence of psychological morbidities and associated coping styles during the COVID-19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The confirmatory Factor Analysis and exploratory analysis allowed to assess the structure of the (GHQ-28) sub-scales in Peruvian population not psychiatric. In Table 2, the quantitative analysis is shown, we found that global averages varied for the subscales of anxiety/insomnia and social dysfunction, whose means are high and are between (M= 1.01; DE = 0.885) and (M= 1.21; DE = 0.942) for items (1, 5, 8, 9, 10, 11, 15, 16, 17, 18, 20, 21).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The confirmatory Factor Analysis and exploratory analysis allowed to assess the structure of the (GHQ-28) sub-scales in Peruvian population not psychiatric. In Table 2, the quantitative analysis is shown, we found that global averages varied for the subscales of anxiety/insomnia and social dysfunction, whose means are high and are between (M= 1.01; DE = 0.885) and (M= 1.21; DE = 0.942) for items (1, 5, 8, 9, 10, 11, 15, 16, 17, 18, 20, 21).…”
Section: Resultsmentioning
confidence: 96%
“…Each item is graded on a 4-point scale to identify the severity of symptoms between 0 and 3 (“Not at all”, “No more than usual”, “More than usual” and “Much more than usual”). This version contains 4 subscales: somatic symptoms, anxiety, insomnia, social dysfunction, and severe depression (1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations